Psychological health in competitive volleyball players: a systematic review of stress, competitive anxiety, and well-being - Rudyanto Rudyanto; Andre Igoresky; Ardo Okilanda (JRTI (Jurnal Riset Tindakan Indonesia), 2025)
Competitive volleyball certainly involves rigorous training schedules and no shortage of competitions, which put heavy psychological demands on players. Still, when one considers the psychological health of volleyball players, little has been done in comparison to the physical and technical performance aspects. This systematic review has two objectives: 1) to summarize research on psychological stress, competitive anxiety, and psychological well-being of competitive volleyball players, and 2) to explore ways of assessment, factors influencing, and intervention of these psychological states. Using the latest version of PRISMA guidelines for conducting systematic reviews, the records retrieved are 721 in total. With the removal of three duplicates, 718 studies were screened. 72 full-text studies were assessed, and finally, 10 studies met the inclusion criteria and were included in qualitative synthesis. Four major themes were identified. First, higher levels of perceived stress and training-load strain were linked to poorer recovery and lower well-being. Second, anxiety related to competition and the period just before the competition was sensitive to changes resulting from psychophysiological measures and neuromodulatory interventions. Third, sleep quality and personal well-being reflected important indicators of injury risk and mental-health status. Fourth, internal motivational resources, social support, and resilience were the factors that strengthened the athletes' capacity to handle stress and anxiety. These results provide support for existing theoretical models of athlete stress and point out the significance of ongoing psychological assessment and tailored mental-health assistance in volleyball programs. Further studies should concentrate on longitudinal and experimental research studying the associations among psychological variables, performance, and athlete well-being.